Causes, consequences, and reversal of immune system aging - Montecino-Rodriguez, Encarnacion (American Society for Clinical Investigation, 2013)
The effects of aging on the immune system are manifest at multiple levels that include reduced production of B and T cells in bone marrow and thymus and diminished function of mature lymphocytes in secondary lymphoid tissues. As a result, elderly individuals do not respond to immune challenge as robustly as the young. An important goal of aging research is to define the cellular changes that occur in the immune system and the molecular events that underlie them. Considerable progress has been made in this regard, and this information has provided the rationale for clinical trials to rejuvenate the aging immune system.